Software agent for economic sustainability assessment of recycling technology - Sheng, Yunzhou. (2011)
This report presents the design and development of a software agent dedicated to providing industrial users with a forecast and evaluation tool for nickel recovery process in the economic and environmental aspects. A nickel recovery process has been developed by SIMTech for the local recycling companies, recovering nickel from industrial spent catalyst NiO compound. Incorporating the existing process model, the software agent focuses on taking into consideration of the uncertain inputs, such as nickel market price and NiO compound emission factor, and analyzing the economic profitability and carbon emissions of the process.